Early diagnosis of fibrotic interstitial lung disease: challenges and opportunities. Issue 9 (September 2021) - Spagnolo, Paolo; Ryerson, Christopher J; Putman, Rachel; Oldham, Justin; Salisbury, Margaret; Sverzellati, Nicola; Valenzuela, Claudia; Guler, Sabina; Jones, Steve; Wijsenbeek, Marlies; Cottin, Vincent
Summary: Many patients with interstitial lung disease (ILD) develop pulmonary fibrosis, which can lead to reduced quality of life and early mortality. Patients with fibrotic ILD often have considerable diagnostic delay, and are exposed to unnecessary and costly diagnostic procedures, and ineffective and potentially harmful treatments. Non-specific and insidious presenting symptoms, along with scarce knowledge of fibrotic ILD among primary care physicians and non-ILD experts, are some of the main causes of diagnostic delay. Here, we outline and discuss the challenges facing both patients and physicians in making an early diagnosis of fibrotic ILD, and explore strategies to facilitate early identification of patients with fibrotic ILD, both in the general population and among individuals at highest risk of developing the disease. Finally, we discuss controversies and key uncertainties in screening programmes for fibrotic ILD. Timely identification and accurate diagnosis of patients with fibrotic ILD poses several substantial clinical challenges, but could potentially improve outcomes through early initiation of appropriate management.